2003
DOI: 10.1046/j.1365-294x.2003.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genetic study confirms exceptionally low genetic variation in the ancient and endangered relictual conifer, Wollemia nobilis (Araucariaceae)

Abstract: The Wollemi pine, Wollemia nobilis (Araucariaceae), was discovered in 1994 as the only extant member of the genus, previously known only from the fossil record. With fewer than 100 trees known from an inaccessible canyon in southeastern Australia, it is one of the most endangered tree species in the world. We conducted a comparative population genetic survey at allozyme, amplified fragment length polymorphism (AFLP) and simple sequence repeat (SSR) loci in W. nobilis, Araucaria cunninghamii and Agathis robusta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 49 publications
1
72
2
1
Order By: Relevance
“…Such high levels of diversity may have resulted from the species not having been strongly affected by genetic drift and/or inbreeding processes, because their population sizes may never have been reduced below a certain threshold. Similarly, narrowly distributed species do not necessarily demonstrate high differentiation among populations (Gitzendanner and Soltis 2000;Peakall et al 2003). Life history traits (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Such high levels of diversity may have resulted from the species not having been strongly affected by genetic drift and/or inbreeding processes, because their population sizes may never have been reduced below a certain threshold. Similarly, narrowly distributed species do not necessarily demonstrate high differentiation among populations (Gitzendanner and Soltis 2000;Peakall et al 2003). Life history traits (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…However, experimental evidence has not always supported this generalization (see Peakall, Ebert, Scott, Meagher, & Offord, 2003; Vanden‐Broeck et al., 2011). Low rates of evolution, genetic stability, and habitat reliability have been proposed as some of the factors that may influence the genetic patterns of relict species (Hampe & Petit, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…C. Moreno et al / Forest Systems (2011) 20(2), 303-314 et al, (from Scott et al, 2003 nomic homology is likely to translate into greater conservation of SSR flanking regions and, as a result, in higher transferability of primer pairs (Rossetto, 2001). Studies within the Araucariaceae family showed a very low genetic variability among and within species (Peakall et al, 2003;Scott et al, 2005). Moreover, after sequencing, similar structure of the microsatellite stretches and a high sequence conservation of the flanking regions was observed among several species of Araucariaceae .…”
Section: Discussionmentioning
confidence: 84%